Detección del virus del papiloma humano en orina. Evaluación de calidad de los metaanálisis - Gonzalez Mariño, Mario Arturo (2026)
A methodological quality assessment was conducted on meta-analyses investigating the detection of human papillomavirus (HPV) in urine samples. A systematic review of meta-analyses was performed using the search term “HPV in urine” in the PubMed, Embase, and Scopus databases. After removing duplicates and studies unrelated tothe topic or not meta-analyses during the title and abstract screening, seven studies were included for analysis. The methodological quality of the selected meta-analyses was assessed using the AMSTAR 2 tool, and all were classified as critically low quality.Although the results of these metanalyses suggest that HPV DNA detection in urine could be useful for identifying cervical HPV infection, the significant methodological limitations observed substantially reduce confidence in their conclusions. Overall,the assessment showed that overall confidence in the results was critically low